Blood-brain barrier dysfunction in disorders of the developing brain - Moretti, Raffaella; Pansiot, Julien; Bettati, Donatella; Strazielle, Nathalie; Ghersi-Egea, Jean-François; Damante, Giuseppe; Fleiss, Bobbi; Titomanlio, Luigi; Gressens, Pierre (Frontiers in Neuroscience, 2015)
ABSTRACT Disorders of the developing brain represent a major health problem. The neurological manifestations of brain lesions can range from severe clinical deficits to more subtle neurological signs or behavioral problems and learning disabilities, which often become evident many years after the initial damage. These long-term sequelae are due at least in part to central nervous system immaturity at the time of the insult. The blood brain barrier (BBB) protects the brain and maintains homeostasis. BBB alterations are observed during both acute and chronic brain insults. After an insult, excitatory amino acid neurotransmitters are released, causing reactive oxygen species (ROS)-dependent changes in BBB permeability that allow immune cells to enter and stimulate an inflammatory response. The cytokines, chemokines and other molecules released as well as peripheral and local immune cells can activate an inflammatory cascade in the brain, leading to secondary neurodegeneration that can continue for months or even years and finally contribute to post-insult neuronal deficits. The role of the BBB in perinatal disorders is poorly understood. The inflammatory response, which can be either acute (e.g. perinatal stroke, traumatic brain injury) or chronic (e.g. perinatal infectious diseases) actively modulates the pathophysiological processes underlying brain injury. We present an overview of current knowledge about BBB dysfunction in the developing brain during acute and chronic insults, along with clinical and experimental data.